Clinical Case Studies in Psychoanalytic and Psychodynamic Treatment - Willemsen, Jochem; Della Rosa, Elena; Kegerreis, Sue (Frontiers in Psychology, 2017)
This manuscript provides a review of the clinical case study within the field of psychoanalytic and psychodynamic treatment. The method has been contested for methodological reasons and because it would contribute to theoretical pluralism in the field. We summarize how the case study method is being applied in different schools of psychoanalysis, and we clarify the unique strengths of this method and areas for improvement. Finally, based on the literature and on our own experience with case study research, we come to formulate nine guidelines for future case study authors: 1) basic information to include, 2) clarification of the motivation to select a particular patient, 3) information about informed consent and disguise, 4) patient background and context of referral or self-referral, 5) patient’s narrative, therapist’s observations and interpretations, 6) interpretative heuristics, 7) reflexivity and counter-transference, 8) leaving room for interpretation, and 9) answering the research question, and comparison with other cases.